2017
DOI: 10.1016/s2213-8587(17)30307-8
|View full text |Cite
|
Sign up to set email alerts
|

Omega-6 fatty acid biomarkers and incident type 2 diabetes: pooled analysis of individual-level data for 39 740 adults from 20 prospective cohort studies

Abstract: Summary Background The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes. Methods We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
159
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(191 citation statements)
references
References 31 publications
24
159
3
5
Order By: Relevance
“…Our finding that a higher relative concentration of omega-6 fatty acids was associated with decreased diabetes risk, whereas higher MUFA levels were associated with increased diabetes risk is consistent with previous investigations (29,30). Consistent with our results in young adults, a recent large-scale study pooling data from 20 prospective cohorts reported that higher levels of linoleic acid, the predominant omega-6 fatty acid, has long-term benefits for the prevention of type 2 diabetes (30). These fatty acids are likely reflective of both dietary composition and endogenous metabolism (31).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that a higher relative concentration of omega-6 fatty acids was associated with decreased diabetes risk, whereas higher MUFA levels were associated with increased diabetes risk is consistent with previous investigations (29,30). Consistent with our results in young adults, a recent large-scale study pooling data from 20 prospective cohorts reported that higher levels of linoleic acid, the predominant omega-6 fatty acid, has long-term benefits for the prevention of type 2 diabetes (30). These fatty acids are likely reflective of both dietary composition and endogenous metabolism (31).…”
Section: Discussionsupporting
confidence: 93%
“…LA biosynthesis and metabolism requires some of the same enzymes used for EPA synthesis and metabolism, including the production of downstream metabolites 32,33 . Moreover, LA's consumption in the western diet is [14][15][16][17][18] times the amount required to prevent LA deficiency 22,46 and LA's effects on insulin sensitivity are strongly debated [46][47][48][49][50][51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent meta-analysis that consisted of 39,740 adults, only higher levels of 18:2n-6, but not 20:4n-6, were associated with a lower risk of type 2 diabetes (7). Moreover, inconsistent associations of 22:4n-6 or 22:5n-6 with CHD or type 2 diabetes were also reported in cohort studies among European populations (30,32).…”
Section: Continuedmentioning
confidence: 97%